Selección de Access Point en redes inalámbricas 802.11 garantizando mínima capacidad para QoS basado en control de potencia (2014)
In this paper we model a wireless network as a static, non-cooperative game in which users seek to obtain its minimum capacity through the choice of an Access Point. Particularly, this paper proposes an algorithm that seeks to make the selection of the wireless access point that will guarantee a high Quality of Service ( QoS ) based on ability for all users in 802.11 net-works, ensuring transfer rates required for any network task , tending the lowest possible energy consumption. According to game theory, there are many solution concepts, but for this particular case we use the concept of efficient satisfaction equilibrium, which guarantees the objective. The result of the analysis of the model proposed and applied game theory, is an algorithm that allows access point selection using the concept of efficient satisfaction equilibrium, which guarantees service quality from the perspective of capacity , minimizing energy consumption . Finally we conclude that it is possible to improve the mechanism of selection and access point association in 802.11 networks by implementing algorithms that articulate the quality of service to energy efficiency, above, as a possible contribution to the development of radio standard cognitive 802.11 networks